Applying a humanistic pedagogy to advance and integrate humane values in a medical school environment - M. P. Jama (Perspectives in Education, 2018)
Sometimes universities in general are criticised because of impersonal campus environments, or “academic incivility”. However, research shows that this phenomenon is more common in medical schools, pointing to increased levels of stress and incidences of attempted suicide among medical students. The decay in humanitarian attitudes and decline in humane values contribute to stress, although some academics believe that this type of environment is normal for medical students. To confront this criticism, academics should not only focus on cognitive aspects, but also adopt a humanistic pedagogy by integrating humane values in curricular and co-curricular activities of the academic environment. The aim of this paper is to illustrate how a humanistic pedagogy is applied in a Medical School in South Africa, by sharing narratives collected from medical teachers who advance and integrate humane values such as, care, empathy and love in their teaching practice.